Warriors at White Rock: White Rock Township and White Rock City, Republic County, Kansas, 1862-1926 - Clark, Tyler (Kansas State University. Dept. of History, 2011)
The White Rock Valley in Republic County saw Indian violence from both the Cheyenne and the Pawnee. This essay traces the founding of the town of White Rock City and its decline during the railroad years. The vital early years of the town are connected intimately to many Native American stories and records. The author discusses settler perceptions that they eventually "outlasted the Indians."
Keywords: Republic County; White Rock City; White Rock Township; Indian raids; Pawnee